Birth of a female kid from in-vitro matured and fertilized caprine oocytes - KHARCHE, S D; GOEL, A K; SINHA, N K (The Indian Journal of Animal Sciences, 2011)
The aim of the present investigation was to study the survival of in-vitro produced caprine embryos resulting from in-vitro maturation, fertilization and culture in a medium supplemented with estrus goat serum prepared in the laboratory. Ovaries (114) were collected in 5 different trials from local abattoir and transported within 4 h to the laboratory in warm saline (37°C) containing 100 IU penicillin-G and 100 μg streptomycin sulphate/ml. Oocytes were retrieved by follicle puncture technique from goat ovaries. Cumulus oocyte complexes (285; COCs) were selected for in-vitro maturation, fertilization and culture (IVMFC). Oocytes were matured in TCM–199 medium supplemented with 20% estrus goat serum at 38.5°C and 5% CO2 under humidified air for 27 h. After 27 h of in-vitro maturation, oocytes were co-incubated with 1×106 spermatozoa/ml from Sirohi buck in fertilization TALP (20% EGS and 10 μg/ml heparin). Fertilized oocytes were cultured in a 50 μl drop of embryo development medium containing 10% goat serum and 3% BSA along with oviductal epithelial cells for 84–96 h. Four 8–16 cell stage good quality embryos were transferred into each of the 5 non-descript recipient does at the tip of the uterine horn/uterotubal junction through surgical technique. The recovery of culturable oocytes was 2.50/ovary. The maturation rate, cleavage rate and percentage of 8–16 cell stage embryo development were 68.42, 42.56 and 28.91%, respectively. Following transfer, 1 out of 5 recipients became pregnant and delivered a normal healthy female kid weighing 3.15 kg after a gestation period of 146 days. The results indicated that supplementation of estrus goat serum for in-vitro maturation, fertilization and embryo culture for subsequent embryo transfer of in-vitro produced embryos resulted in successful birth of an IVMFC-ET kid.